(untitled) (Kairaranga, 2024)
Handicapped, special, or diverse? Segregated, mainstreamed, or included? The field of disability and difference within education, is vast and wide-ranging. This review of the literature highlights how, although we have come far in the last 40 years, there is still much to learn about effective inclusion of disabled children in early childhood settings. The article compares literature between two distinct decades – the 1980s and the 2010s – identifying the shifts within the field around language, social development of, and attitudes toward, disabled children in early childhood settings. Although international literature is used, the discussion focuses on the Aotearoa New Zealand context. The importance of teachers is acknowledged as a predictor of a positive and inclusive learning environment where disabled children can thrive and succeed.